Proprioceptive training in handball - Acsinte, A. (EHF Scientific Conference 18.-19.11.2011, Wien, Österreich, 2011)
Proprioception is the body`s ability to get information to the brain in response to a stimulus arising within the body; it also refers to the body`s ability to sense the position of its limbs at any moment. For example, an athlete who has gone airborne and then lands on an opponent`s foot may injure his/her ankle if his/her brain does not sense that he/she is landing on someone`s shoe and not the floor.